Evaluasi Kebijakan PPKM Level 4 Dampaknya Terhadap Sosial Ekonomi Masyarakat di Kelurahan Kanigaran Kota Probolinggo - Siti Marwiyah; Widia Sari; Murtias Puji; Maudatul Melidia; Zairotul Hasanah (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
The government has set a new policy related to the increasing growth rate of covid 19, especially on the islands of Java and Bali, because the rate of transmission of the Covid-19 virus is expected to be higher due to the high mobility of citizens during the Eid holidays and the new variant of SARS-CoV-2 (Delta). Wednesday, July 5, 2021, recorded a daily addition of 29,745 new cases. The highest Covid-19 (daily) transmission on July 6, 2021, was recorded at 31,189 cases. The research method used is a descriptive qualitative method that aims to explain, reveal and get a proper description of the PPKM level 4 policy on the economy of the Kanigaran Village community, Probolinggo City. The location determination is based on group considerations, to find out how a level 4 PPKM policy will affect the field economy. However, many people are also not happy with the policy because it causes a decline in the economy or income. One of them is Kanigaran Village around Glaser Plaza and Roundabout. There was a road closure that was closely guarded by the Police and Satpot PP so that people who wanted to enter the area had to know the system when the road was opened and closed. The impact of the PPKM level 4 policy which has been implemented since July 6, 2021, has indeed affected the economy of the community, including those who risk their income from trading results.